Target Dysbiosis of Gut Microbes as a Future Therapeutic Manipulation in Alzheimer’s Disease - Zhu, Feiqi; Li, Chunrong; Chu, Fengna; Tian, Xiaoping; Zhu, Jie (Frontiers in Aging Neuroscience, 2020)
Abstract Alzheimer´s disease (AD) is common age-associated dementia with neurodegeneration. The pathogenesis of AD is complex and still remains unclear. The inflammation, amyloid β (Aβ) and neurofibrillary tangles as well misfolded tau protein in brain may contribute to the occurrence and development of AD. Compared with tau protein, Aβ is less toxic. So far all efforts made in the treatments of AD with targeting these pathogenic factors were unsuccessful over past decades. Recently many studies demonstrated that changes of intestinal environment and gut microbiota via gut-brain axis pathway can cause neurological disorders, such as AD, which may be involved in the pathogenesis of AD. Thus, the remodeling the gut microbiota by various ways to maintain their balance might be a novel therapeutic strategy for AD. In the review, we analyze the characteristics of gut microbiota and its dysbiosis in AD and its animal models, and investigate the possibility of targeting the gut microbiota in treatment of the patients with AD in the future.